IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU PADA SISWA KELAS XI UPW A SMK NEGERI 1 SINGARAJA TAHUN PELAJARAN 2020/2021 - I Nyoman Sumeyasa (Daiwi Widya, 2022)
AbstractThis study aimed at increasing the activity and learning achievement of Hindu Religious Education through the implementation of STAD (Student Teams Achievement Division) - Cooperative learning model. This research was classroom action research. The subject of this research were class XI UPW A students of SMK Negeri 1 Singaraja for the Academic Year 2020/2021 with a total of 35 students as the research targets. Data collection in this study was carried out by observing student activities and learning achievement tests. The data obtained were then analyzed using descriptive analysis methods. The research results obtained in cycle I average score reached 70, while in the implementation of cycle II the class average increased to 82. The absorption level of the students in the implementation of Cycle I was only 70%, while in Cycle II the absorption increased to 82%. And for learning completeness in the implementation of Cycle I was only 47%, and in Cycle II it increased 91%. Based on these data, it can be concluded that the implementation of STAD (Student Teams Achievement Division) - Cooperative learning model can increase learning activity and achievement in Hindu Religious Education.Keywords: Cooperative, STAD, activity, learning achievement